Who was Paul Revere? - Edwards, Roberta; Illustrated by O'Brien, John (New York Penguin Workshop, 2011)
A biography of the patriot of the Revolution who had many trades, among them silver work, manufacture of copper, casting of bells, engraving, and dentistry.
Include Illustration
Keywords: Statesmen -- Massachusetts -- United States